Pattern of adverse drug reactions with chemotherapeutic drugs in a tertiary care hospital of North India: a retrospective study - Jindal, Amita; Brar, B. K.; Kumar, Raj; Kumar, Sumir; Sidhu, Kiranjit; Kaur, Amandeep; Richa; Raj, Rakesh Tilak (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Adverse drug reactions are important causes of mortality and morbidity in the patients. Early detection, evaluation and monitoring of ADRs is essential to improve public health. Methods: This was an observational, non-interventional and retrospective study conducted at the ADR monitoring centre of a tertiary care hospital of North India. Suspected ADR forms reported over a period of 4 years involving at least one chemotherapeutic drug with at least one dose were analyzed. Results: A total of 261 chemotherapeutic drugs associated ADRs were analyzed. Out of these, maximum numbers of ADRs were reported by males (54%). Maximum reporting was done by Skin and VD department (37.93%). Causality assessment was probable in maximum number of cases (54%). Most common ADRs were skin rashes (21.46%), followed by jaundice, urticaria and fixed drug eruptions. Maximum ADRs were suspected to be caused by Anti tubercular drugs (31.42%) followed by anticancer drugs (14.56%). Conclusions: ADRs due to antibiotics and anticancer drugs is a significant health problem.